2009
DOI: 10.1021/bm9006826
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Degradation, and Cytotoxicity of Multiblock Poly(ε-caprolactone urethane)s Containing Gemini Quaternary Ammonium Cationic Groups

Abstract: Novel cationic biodegradable multiblock poly(ε-caprolactone urethane)s that contain gemini quaternary ammonium side groups on the hard segments were developed. To obtain these polyurethanes, a new L-lysine-derivatized diamine containing gemini quaternary ammonium side groups (GA8) was first synthesized and characterized by Fourier transform infrared spectroscopy (FTIR), nuclear magnetic resonance spectra (NMR), mass spectrometry (MS), and high-resolution mass spectra (HRMS). Then a series of gemini poly(ε-capr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
83
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 73 publications
0
83
0
Order By: Relevance
“…And it is well known that primary amine group has much higher reactivity than hydroxyl group with the isocyanate group under mild conditions [26]. Hence, to obtain new waterborne polyurethane materials with good antibacterial properties, the lysine derivative of GQAS with two primary amine groups EG12 as chain extender was first designed (Scheme 1).…”
Section: Synthesis Of Gqas Chain Extender Eg12mentioning
confidence: 99%
See 2 more Smart Citations
“…And it is well known that primary amine group has much higher reactivity than hydroxyl group with the isocyanate group under mild conditions [26]. Hence, to obtain new waterborne polyurethane materials with good antibacterial properties, the lysine derivative of GQAS with two primary amine groups EG12 as chain extender was first designed (Scheme 1).…”
Section: Synthesis Of Gqas Chain Extender Eg12mentioning
confidence: 99%
“…The strong bands at 1,105 cm -1 are overlapped by the C-O-C stretching vibration adsorption of ether groups in PTMG and PEG [30]. Characteristic peaks around 1,440 cm -1 of C-H deformation vibration in the methyl and methylene groups linked with N positive ions are also observed [26,31], which increase with the increase in GQAS contents. Again, these results demonstrate that these waterborne antibacterial polyurethanes have been successfully synthesized.…”
Section: Synthesis and Bulk Structures Of Gqas Waterborne Polyurethanesmentioning
confidence: 99%
See 1 more Smart Citation
“…24 hours was chosen based on previous literature, which has shown that the PU products of degradations are not cytotoxic at least up to 24 h [41] and [42]. From the results (Fig.…”
Section: In Vitro Cytotoxicity Of Peg400-pu-pcl530 Nps In A549 Cellsmentioning
confidence: 99%
“…In this work, cell viability decrease when SDS and Tween 80 was used as surfactant for the experiments carried out at 5 mg/ml of PEG400-PU-PCL530 are in agreement with those reported by Mendes et al [27], who evaluated cell viability for 24 and 48 h, by MTT and neutral red assays (NR) in the presence of nanoparticles with diameters between 130 and 200 nm, and zeta potential between -6.8 and -19.5 mV, for these conditions, increasing nanoparticles concentration induced cell death for both cell types, suggesting that, a negatively influence on cell viability depend of the nanoparticle type and nanoparticles concentration in the dispersion. Ding et al (2009) [42], evaluated the cytotoxicity of multiblock poly(ε-caprolactone urethane) discs synthesized using Gemini Quaternary Ammonium as cationic surfactant by 3T3 cells. The polymers did not show significant cytotoxicity against fibroblasts.…”
Section: In Vitro Cytotoxicity Of Peg400-pu-pcl530 Nps In A549 Cellsmentioning
confidence: 99%